1971
DOI: 10.1136/bmj.1.5741.152
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Agent for the Induction of Ovulation: Preliminary Trials in Women

Abstract: DiscussionMedazepam, a benzodiazepine, is being used in Europe increasingly for the symptomatic relief of neurotic anxiety, but there have been relatively few carefully controlled trials comparing it with established anti-anxiety drugs. The results of our initial investigation on inpatients confirm that it is effective in relieving anxiety. The optimum dose was 10 mg three times a day, and since there were no abnormalities in liver function or blood tests in this group the drug was considered to be safe for ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
5

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(56 citation statements)
references
References 7 publications
0
51
0
5
Order By: Relevance
“…The drug was found to be an extremely potent postcoital contraceptive in the rat [4,5]. Unfortunately, ICI 46,474 did not exhibit antifertility properties in women, in fact, quite the opposite, it induced ovulation [6,7]. As a result, the medicine was, at one time, marketed in the United Kingdom for the induction of ovulation in subfertile women with a functional hypothalamo-pituitary-ovarian axis.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…The drug was found to be an extremely potent postcoital contraceptive in the rat [4,5]. Unfortunately, ICI 46,474 did not exhibit antifertility properties in women, in fact, quite the opposite, it induced ovulation [6,7]. As a result, the medicine was, at one time, marketed in the United Kingdom for the induction of ovulation in subfertile women with a functional hypothalamo-pituitary-ovarian axis.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…Regarding the time interval between the commencement of treatment and ovulation, Klopper and Hall (1971) reported the period of 6 to 20 days after the oral administration (10 days on average), and Macourt (1974) did a lag of 6 to 20 days (11 days on average). Our results were similar to those reported by Williamson and Ellis (1973) and Tajima et al (1977) and the time lag was between day 13 and 46 of the treatment, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Since ovulation-inducing effect of tamoxifen was firstly proved by Klopper and Hall (1971) (1977,1978,1979). An ovulatory induction rate of 73.3% in the present study is consistent with the results reported by those investigators, which ranged between 61.2 and 81.3% with an exception of 95% repored by Ruiz-Velasco et al (1979).…”
Section: Discussionmentioning
confidence: 99%
“…Walpole advanced clinical testing of ICI 46,474 in both "the control of hormone dependent tumours" and "the regulation of the sexual cycle." Clinical testing was initiated to evaluate activity to treat breast cancer at the Christie Hospital in Manchester and the Princess Margaret Hospital, Birmingham (13,14) and reproductive cycle studies proceeded elsewhere (15). In 1972, all conclusions were reviewed by ICI Ltd Pharmaceuticals Division in Alderley Park, Macclesfield, Cheshire.…”
Section: Tamoxifen (Ici 46474) Before Targetingmentioning
confidence: 99%
“…Unlike the results observed in the rat, ICI 46,474 (16) was not a contraceptive in humans. The drug induced ovulation and could potentially be used as a profertility agent (15). ICI 46,474 exhibited modest activity as a breast cancer therapy which was equivalent to historical controls treated with high dose oestrogens or androgens (13).…”
Section: Tamoxifen (Ici 46474) Before Targetingmentioning
confidence: 99%